2015
DOI: 10.1016/j.ebiom.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Predictive Biomarkers of Survival for Non-small Cell Lung Cancer Patients Undergoing Radical Radiotherapy: Two Proteins With Predictive Value

Abstract: Lung cancer is the most frequent cause of cancer-related death world-wide. Radiotherapy alone or in conjunction with chemotherapy is the standard treatment for locally advanced non-small cell lung cancer (NSCLC). Currently there is no predictive marker with clinical utility to guide treatment decisions in NSCLC patients undergoing radiotherapy. Identification of such markers would allow treatment options to be considered for more effective therapy. To enable the identification of appropriate protein biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…For example, alpha‐1‐acid glycoprotein 1 (ORM1) has been detected in non‐small cell lung cancer and gastric adenocarcinoma, and apolipoprotein A‐IV (APOA4) in ovarian and pancreatic cancers . Likewise, many studies have reported elevated inflammatory markers, such as C reactive protein (CRP) and/or Serum amyloid A‐1 protein (SAA1) . For example, in plasma of patients with lung and liver cancer, and elsewhere in relation to circulation and cardiovascular risk, including atherosclerosis and aortic aneurysms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alpha‐1‐acid glycoprotein 1 (ORM1) has been detected in non‐small cell lung cancer and gastric adenocarcinoma, and apolipoprotein A‐IV (APOA4) in ovarian and pancreatic cancers . Likewise, many studies have reported elevated inflammatory markers, such as C reactive protein (CRP) and/or Serum amyloid A‐1 protein (SAA1) . For example, in plasma of patients with lung and liver cancer, and elsewhere in relation to circulation and cardiovascular risk, including atherosclerosis and aortic aneurysms.…”
Section: Methodsmentioning
confidence: 99%
“…67 Likewise, many studies have reported elevated inflammatory markers, such as C reactive protein (CRP) and/or Serum amyloid A-1 protein (SAA1). 81,[83][84][85] For example, in plasma of patients with lung and liver cancer, and elsewhere in relation to circulation and cardiovascular risk, 41,86,87 including atherosclerosis and aortic aneurysms.…”
Section: Differentially Abundant Proteinsmentioning
confidence: 99%
“…This protein was further validate using a bigger cohort, which implicates the immune system as a potential mediator of doxorubicin‐ and trastuzumab‐induced cardiac dysfunction. Plasma has also been used to evaluate the effect of radiotherapy toxicity in lung cancer, and to study the proteome profiles of fatigued men with non‐metastatic prostate cancer exposed to beam radiation . In these studies, patients were sampled before the treatment, and the sampling then went on for several days or months.…”
Section: Protein Expressionmentioning
confidence: 99%
“…As an example, the results obtained by Walker et al. suggest that the combination of the expression of C‐reactive protein (CRP) and leucine‐rich alpha‐2‐glycoprotein 1 is related with an extended survival post radiotherapy treatment for locally advanced non‐small cell lung cancer . Wider time frames have been used to monitor the expression of apolipoproteins during pregnancy (up to several weeks), or to evaluate candidate biomarkers for ischemic stroke (up to 1 year), the last study showing that fibrinogen and CRP proteins have expression profiles with potential clinical utility.…”
Section: Protein Expressionmentioning
confidence: 99%
“…A combination of CRP and LRG1 gave a highly significant indication of extended survival post 1 week of radiotherapy treatment, proposing these proteins may be predictive marker to guide treatment decisions in NSCLC patients undergoing radiotherapy. [12] Targeted therapy is an important therapeutic strategy in NSCLC treatment. However, the sensitivity and resistance to a targeted therapy varies among patients with different molecular pathologies.…”
Section: Application Of Proteomics In Non-small-cell Lung Cancermentioning
confidence: 99%